A COMPARATIVE STUDY OF CHANDRALEKHA AND MARINA ABRAMOVIĆ: CHALLENGING NORMS THROUGH THE FEMALE BODY IN PERFORMANCE - Sreeparvathi .D; Rincy T P (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper compares two seminal performance artists, Indian choreographer and dancer Chandralekha and Serbian performance artist Marina Abramović. They both changed how the female body is used in modern art. Even though they came from very different cultural and political backgrounds, both artists used the body as the focus of their creative expression to question mainstream ideas about aesthetics, gender, and politics. Chandralekha used the classical Indian dance style Bharatanatyam as a base and added aspects of yoga, martial arts, and Tantric philosophy to her work to reclaim women’s sexuality, strength, and political presence. Marina Abramović, who works in the global avant-garde art world, used endurance, vulnerability, and audience participation to show how power works in violence, objectification, and spectatorship. The study says that both artists used their bodies not as something to portray but as active sites of resistance and change, based on ideas of performativity, embodiment, and resistance. The study looks at works like Chandralekha’s Sri and Abramović’s Rhythm 0 and The Artist Is Present to see how embodied performance can shake up cultural scripts and provide women and political activists new ways to express themselves. The study ends by saying that Chandralekha and Abramović, although though they come from different backgrounds and have different practices, both use the body as a revolutionary tool to challenge and change the definitions of gender, tradition, and presence.